1975
DOI: 10.1111/j.1151-2916.1975.tb18973.x
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Limit of La in the Lead Zirconate‐Titanate System

Abstract: The disappearing-phase method was used to determine the extent of the solid-solution region of the PLZT system for conventionally sintered ceramics prepared at 1100" and 1300°C in a PbO atmosphere provided by WZrO,. A decrease in the firing temperature from 1300" to 1100°C lowers the solubility limit by 5 to 8 at.% La. Beyond the limits of solubility, additional La forms LazZrzO7 and/or LazTizO,. The limit determined by the disappearing-phase method (1300°C firing) is compared to values determined by the param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

1975
1975
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 7 publications
3
10
0
Order By: Relevance
“…However, some La‐rich compositions also contained small amounts of La 2 Zr 2 O 7 . The amount of La 2 Zr 2 O 7 can vary for different sintering procedures, but because the sintering took place at a high temperature (1325°C) the solubility of La 2 Zr 2 O 7 was near maximal 15 . Most of the PLZT materials consisted of a single phase, but a few showed that they contained a mixture of two PLZT phases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some La‐rich compositions also contained small amounts of La 2 Zr 2 O 7 . The amount of La 2 Zr 2 O 7 can vary for different sintering procedures, but because the sintering took place at a high temperature (1325°C) the solubility of La 2 Zr 2 O 7 was near maximal 15 . Most of the PLZT materials consisted of a single phase, but a few showed that they contained a mixture of two PLZT phases.…”
Section: Resultsmentioning
confidence: 99%
“…The most striking difference between the present and reported results is the position of the region of the mixed phases according to Haertling 1 . The present method of the synthesis included high temperatures; therefore, the solubility of La 2 Zr 2 O 7 in PLZT was at a maximum 15 …”
Section: Resultsmentioning
confidence: 99%
“…Based on thermodynamic considerations, a sophisticated buffering system, consisting of a mixture of PbZrO 3 and ZrO 2 , was designed by Holman and Fulrath as well as Kingon and Clarke . Although originally derived for undoped PZT, the system works well for doped PZT materials with moderate dopant content . Along with the technological development of raw materials technology and the introduction of high energy ball milling, calcination temperatures could be decreased and PZT powders in or close to the submicron range became technological standard .…”
Section: Introductionmentioning
confidence: 99%
“…A similar experiment carried out by Xia and Yao 11 showed that Pb(Zn 1/3 Nb 2/3 )O 3 sintered in an atmosphere containing sufficient PbO experienced an intergranular fracture, presumably because of the PbO in the grain boundary, whereas the PbO‐depleted structure was porous and had an intragranular fracture. When La was substituted for Pb in the PZT structure, it was found 17 that ZrO 2 and/or La 2 Zr 2 O 7 could be formed. However, the presence of La 2 Zr 2 O 7 may not necessarily be a sign of PbO depletion; it could also be caused by a low temperature during sintering 17 .…”
Section: Introductionmentioning
confidence: 99%
“…When La was substituted for Pb in the PZT structure, it was found 17 that ZrO 2 and/or La 2 Zr 2 O 7 could be formed. However, the presence of La 2 Zr 2 O 7 may not necessarily be a sign of PbO depletion; it could also be caused by a low temperature during sintering 17 . Further heating would then make La 2 Zr 2 O 7 disappear.…”
Section: Introductionmentioning
confidence: 99%